2015
DOI: 10.1007/s11145-015-9571-2
|View full text |Cite
|
Sign up to set email alerts
|

“If I point, do they look?”: The impact of attention–orientation strategies on text exploration during shared book reading

Abstract: The current study examined the effect of pointing to the words and using highlighted text by examining eye movements when children in preschool, Grade 1 and 2 were read storybooks of two levels of difficulty. For all children, pointing to and highlighting the text was observed to increase the amount of time and number of fixations on the printed text than when there was no intervention. Furthermore, with difficult text, an increased amount of time and number of fixations was observed when the text was pointed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Similarly, Roy‐Charland and colleagues found that when preschool‐aged children were encouraged to look at the text through highlighting or pointing, they did increase their attention to the print, but only at mismatched times. For all preschool‐aged participants but one, the focus was exclusively on the illustrations for the narrative portion of shared reading (Roy‐Charland, Perron, Boulard, Chamberland, & Hoffman, ). Furthermore, preschool children's attention to illustrations has been shown to be highly dependent on their prior knowledge, with children attending more to illustrations of words they understood and learning more new words from illustrations they attend to (Evans & Saint‐Aubin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Roy‐Charland and colleagues found that when preschool‐aged children were encouraged to look at the text through highlighting or pointing, they did increase their attention to the print, but only at mismatched times. For all preschool‐aged participants but one, the focus was exclusively on the illustrations for the narrative portion of shared reading (Roy‐Charland, Perron, Boulard, Chamberland, & Hoffman, ). Furthermore, preschool children's attention to illustrations has been shown to be highly dependent on their prior knowledge, with children attending more to illustrations of words they understood and learning more new words from illustrations they attend to (Evans & Saint‐Aubin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dialogic techniques include providing definitions (Coyne, Simmons, Kame'enui, & Stoolmiller, ), asking children questions (Walsh & Blewitt, ), and asking children to point to items on the page (Sénéchal et al, ). During shared storybook reading, adult pointing helps children attend to specific items (Roy‐Charland et al, ) and facilitates vocabulary growth (Sénéchal, ). Here, we demonstrate another nonpointing gesture also facilitates word learning from storybooks.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in an eye‐tracking study, Justice, Skibbe, Canning, and Lankford () found that 4‐year‐old pre‐school children looked longer at the illustrations than the print that accompanied complicated texts, indicating that even with some emerging print awareness, children look primarily at illustrations. In another eye‐tracking study, Evans and Saint‐Aubin () found that even with a range of illustration styles, preschool children spent the majority of their time looking at illustrations and only 6% of their time looking at the printed text (for similar findings, see, e.g., Roy‐Charland, Perron, Boulard, Chamberland, & Hoffman, ; Roy‐Charland, Saint‐Aubin, & Evans, ).…”
Section: Introductionmentioning
confidence: 85%
“…Preschool‐aged children attend to illustrations over print more than 90% of the time (e.g., Evans & Saint‐Aubin, ; Justice, Skibbe, Canning & Lankford, ), but children who know more words and letters attend more to words and letters (Evans, Saint‐Aubin & Landry, ). Even when prompted to attend to print, however, preschool‐aged children attend to illustrations during the narrative and only focus on the text at mismatched times (Roy‐Charland, Perron, Boulard, Chamberland & Hoffman, ). Importantly, preschoolers attend longer to illustrations that are represented by more text (Evans & Saint‐Aubin, ), and when the text is manipulated to emphasise a particular element of the illustration, preschool children attend more to the highlighted portion (Evans & Saint‐Aubin, ).…”
Section: Highlightsmentioning
confidence: 99%